The Impact of Cash Management Practices toward Financial Performance of Small and Medium Enterprises in Indonesia - Amini, Nuzulia; Setiono, Bambang; Pangaribuan, Christian Haposan; Princes, Elfindah (APPS Publications, 2021)
Objective – The importance of SMEs in Indonesia has been becoming the center of attention for the government to help the national economy grow. However, there are still many problems that hinder the potential of SMEs to develop. One of the problems is financial Management in terms of cash management, which can help SMEs have better Management over cash and better performance. Therefore, this study aims to analyze the current two elements of cash management practice, forecasting (FOR) and cash mobilization (CML) done by SMEs in Indonesia and its impact on Return on Assets (ROA) and Gross Profit Margin (GPM) as the financial performance measurements. Methodology – The research uses a quantitative approach from 90 SMEs in Java and Bali islands from April until July 2018. The data were analyzed descriptively using a 4-point scale questionnaire. A regression analysis was added to find out significant relationships between the variables. Findings – The research found that SMEs owners/managers often do forecasting and rarely do cash mobilization practices. The regression analysis shows a significant relationship between cash management practices and ROA but a non-significant relationship between cash management practices and Gross Profit Margin (GPM). Novelty – This research provides an insight of how cash management practices influence the financial performance in the context of SMEs.